2018
DOI: 10.1002/pits.22202
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of school‐based interventions and their outcomes for youth exposed to traumatic events

Abstract: Youth exposed to traumatic events are at higher risk for negative developmental outcomes, including low academic performance, poor social skills, and mental health concerns. To best address these risks, school-based intervention services, and trauma-informed practices can be provided. The goal of this study was to systematically review the intervention research conducted on school-based trauma interventions, with specific attention to examine intervention effectiveness, feasibility, and acceptability across st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…A third macrolevel support refers to various intervention programs aimed at mitigating the impact of youth trauma (Ford, Steinberg, et al, 2012; Scheeringa et al, 2011). Indeed, to synthesize three recent systematic reviews of school-based intervention programs across 171 articles (with some overlapping studies), it appears that long-term programs with a codified curriculum that is co-constructed with caregivers and delivered by trained staff are most effective, although what is still needed are better frameworks for implementing and measuring effectiveness of said programs and protocols for more precise analysis of participant demographics (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A third macrolevel support refers to various intervention programs aimed at mitigating the impact of youth trauma (Ford, Steinberg, et al, 2012; Scheeringa et al, 2011). Indeed, to synthesize three recent systematic reviews of school-based intervention programs across 171 articles (with some overlapping studies), it appears that long-term programs with a codified curriculum that is co-constructed with caregivers and delivered by trained staff are most effective, although what is still needed are better frameworks for implementing and measuring effectiveness of said programs and protocols for more precise analysis of participant demographics (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences. For example, using a race-centered analysis, I found that 85% of the 21 U.S. study samples ( n = 1,359) in Yohannan and Carlson’s (2019) review were composed of students of color; yet almost no intervention programs in the 98 studies Rodger et al (2019) reviewed were specifically designed for students of color.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their systematic review of school-based interventions for young people exposed to traumatic events, Yohannan and Carlson (2019) concluded that trauma intervention literature often does not account for diverse group experiences of trauma and related supports. They recommend that "there are eight dimensions that need to be considered when working with diverse youth and families: language, persons, metaphors, content, concepts, goals, methods, and contexts".…”
Section: Promoting Cultural and Personal Safetymentioning
confidence: 99%